Quality indicators for the diagnosis and antibiotic treatment of acute respiratory tract infections in general practice: a RAND Appropriateness Method - Laura Trolle Saust; Lars Bjerrum; Magnus Arpi; Malene Plejdrup Hansen (Taylor & Francis Group, 2017)
Objective: To develop quality indicators for the diagnosis and antibiotic treatment of acute respiratory tract infections, tailored to the Danish general practice setting. Design: A RAND/UCLA Appropriateness Method was used. Setting: General practice. Subjects: A panel of nine experts, mainly general practitioners, was asked to rate the relevance of 64 quality indicators for the diagnosis and antibiotic treatment of acute respiratory tract infections based on guidelines. Subsequently, a face-to-face meeting was held to resolve misinterpretations and to achieve consensus. Main outcome measures: The experts were asked to rate the indicators on a nine-point Likert scale. Consensus of appropriateness for a quality indicator was reached if the overall panel median rating was 7-9 with agreement. Results: A total of 50 of the 64 proposed quality indicators attained consensus. Consensus was achieved for 12 indicators focusing on the diagnostic process and 19 indicators focusing on the decision about antibiotic treatment and choice of antibiotics, respectively. Conclusion: These newly developed quality indicators may be used to strengthen Danish general practitioners' focus on their management of patients with acute respiratory tract infections and to identify where there is a need for future quality improvements.